Influencia del paquete del sistema de control de gestión en el desempeño de las tareas, moderado por la presencia de recursos financieros en las empresas emergentes - Theiss, Viviane (2023)
This research analyzes the influence of the management control system (MCS) package on task performance, moderated by the presence of financial resources in startups. This is a descriptive study carried out through a survey, with a quantitative approach, based on the analysis of structural equations. The research population consisted of companies associated with ABStartups, with information collected through an electronic questionnaire, with a probabilistic sample consisting of 100 startups. The results showed that the design of the MCS package has a direct and positive effect on the task performance of startups and the presence of financial resources has a moderating effect on the MCS package and task performance in startups. An additional multigroup analysis was carried out between the presence of external and internal financial resources. Among the results, it was verified that, in the external finance group, there was only a positive and significant effect between MCS package design and task performance. In the group of internal financial resources, all relationships are positive and significant, an aspect linked to the generation of information for decision-making, behavioral stimulation and the achievement of the company's objectives.